Applications and Challenges of Machine Learning to Enable Realistic Cellular Simulations - Vasan, Ritvik; Rowan, Meagan P.; Lee, Christopher T.; Johnson, Gregory R.; Rangamani, Padmini; Holst, Michael (Frontiers in Physics, 2020)
In this perspective, we examine three key aspects of an end-to-end pipeline for realistic cellular simulations: Reconstruction and segmentation of cellular structure; Generation of cellular structure; and Mesh generation, simulation, and data analysis. We highlight some of the relevant prior work in these distinct but overlapping areas, with a particular emphasis on current use of machine learning technologies, as well as on future opportunities.